Consciousness and Language - Nasyhovna, Maklakova Evgeniya Mikhaylovna, Farrakhova Gulnaz Faizovna, Slavina Liliya Rustamovna, Mustafina Jamila; Garaeva Rimma Salavatovna, Aydayeva Gunay Firuddinovna, (Opción, 2019)
This review article is devoted to the concept of consciousness in psycholinguistics. The characteristic features of interpretation in related sciences, the use in the process of interpretation of various methods of linguistic analysis are considered. The work covers the approaches to the concept of consciousness on the examples of works of domestic and foreign scientists. The necessity of using the concept of consciousness in combination with the concepts that operate in philosophy, psychology and psycholinguistics is revealed and substantiated. In conclusion, consciousness exists everywhere as a universal phenomenon and has a dual nature, because it is material and ideal.